The Influence Of Career Planning And Adversity Quotient On Job Readiness Of Students (A Study On Management Students Of The 2021 Cohort At Universitas Muhammadiyah Surakarta) - Olivia, Ane; Hakim, Lukman (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
This research explores how career planning and adversity quotient affect the job readiness of management students from the 2021 cohort at Universitas Muhammadiyah Surakarta. A quantitative method was applied, utilizing a survey with a questionnaire distributed to 117 respondents selected through purposive sampling. Career planning and adversity quotient, as the independent variables, and job readiness as the dependent variable were measured using a Likert scale. The study employed various data analysis techniques, including validity and reliability tests, classical assumption checks (normality, multicollinearity, and heteroscedasticity), and multiple linear regression to analyze the relationship between the variables. The findings reveal that both career planning and adversity quotient significantly and positively influence job readiness. However, the study is constrained by a limited sample size and the focus on a single department, which may limit the generalizability of the results. Future studies should include a broader sample of students from various departments and universities, and incorporate other factors such as internship experience, interpersonal and communication skills, and social support, to gain a more holistic view of the factors that impact job readiness.